KONSEP MOTIVASI DASAR DALAM LEMBAGA PENDIDIKAN ISLAM - zainularifin (POJOK GURU: Jurnal Keguruan dan Ilmu Pendidikan, 2023)
Motivation is a stimulus or desire and the driving force of a person's willingness to work. Each motivation has a purpose, direction and individual persistence to be achieved. Motivation can also be interpreted as a process that causes a person's behavior to be passionate, directed, and not easily discouraged. Motivation plays a role in providing encouragement to a person or organization member to work and try to achieve their achievements. Some of the motivational theories described in the description above are actually descriptions to better understand work motivation in an Islamic educational institution. Keyword: Motivation, Islamic Education Institute